The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1128/aac.04132-14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Function Estimation on Pharmacokinetic Modeling of Vancomycin in Elderly Patients

Abstract: Vancomycin is a renally excreted drug, and its body clearance correlates with creatinine clearance. However, the renal function estimation equation that best predicts vancomycin clearance has not been established yet. The objective of this study was to compare the abilities of different renal function estimation equations to describe vancomycin pharmacokinetics in elderly patients. The NPAG algorithm was used to perform population pharmacokinetic analysis of vancomycin concentrations in 78 elderly patients. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Our group has investigated this question in elderly patients for two antimicrobials, gentamicin, and vancomycin, using a population pharmacokinetic approach. For gentamicin, the CG equation better predicted the drug clearance than the MDRD equation , while for vancomycin, the results were comparable except for CKD‐EPI which performed worst . These results and others suggest that a good marker of the GFR is not necessarily a good marker of drug clearance.…”
Section: Discussionmentioning
confidence: 78%
“…Our group has investigated this question in elderly patients for two antimicrobials, gentamicin, and vancomycin, using a population pharmacokinetic approach. For gentamicin, the CG equation better predicted the drug clearance than the MDRD equation , while for vancomycin, the results were comparable except for CKD‐EPI which performed worst . These results and others suggest that a good marker of the GFR is not necessarily a good marker of drug clearance.…”
Section: Discussionmentioning
confidence: 78%
“…SCRs <0.5 mg/dL were set to 0.5 mg/dL to avoid potential bias from an overestimation of renal function and to provide better estimates of vancomycin clearance in patients with low creatinine production . The MDRD and CKD‐EPI equations were adjusted to individual BSA values (GFR = (MDRD or CKD‐EPI) × (BSA/1.73)) to reduce the bias for population prediction . Number of patients with unstable renal function was determined when the eGFR, estimated using the CKD‐EPI equation, decreased by 30 mL/min from the previous or baseline eGFR data.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a renal function estimation equation different from that used in model building could significantly alter the predictive performance for vancomycin PK . The performance of the same population PK model should be compared across various renal function estimation methods to consider the interchangeability of renal function estimation methods in population PK modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study by Tsuji et al found that if the serum creatinine is measured using the Jaffe method, instead of the IDMS method, then a correction of serum creatinine to 0.68 mg/dL is unnecessary within the CG equation [56]. Additionally, a study by Glatard et al found that the CG equation, MDRD equation, and CKD-EPI equations are not interchangeable when calculating vancomycin dosing and prediction of concentrations based on renal function [57]. The authors concluded that whichever equation clinicians utilize to calculate renal function should be the same equation used to dose renally eliminated drugs.…”
Section: Key Clinical Issuesmentioning
confidence: 99%
“…As vancomycin is approximately 90% renally eliminated unchanged in the urine [56, 57], it is imperative to accurately estimate renal function when calculating dosing regimens to help optimize the pharmacokinetic and pharmacodynamic properties of the drug. Cutler et al compared vancomycin kinetics in younger patients (mean age: 23 years) versus older patients (mean age: 68 years) [58].…”
Section: Key Clinical Issuesmentioning
confidence: 99%